The effect of structural preservation conditions on pore structure of marine shale reservoir: a case study of the Wufeng-Longmaxi Formation shale, Southern Sichuan Basin, China - Yu, Weiming; Yuan, Shusheng; Tang, Haoxuan; Luo, Chao; Wu, Wei; Liu, Jia; Yang, Yuran; Zhong, Kesu; He, Liang (Frontiers in Earth Science, 2024)
The marine shale within the Sichuan Basin constitutes China’s significant shale gas production, featuring old formation age, high degree of thermal evolution, multiple tectonic movements, and complex structural conditions. However, there are significant differences in the shale gas preservation conditions and reservoir quality in different areas, limiting future large-scale exploration and development. Pore structure significantly influences shale reservoir quality, gas content, and exploration of shale gas occurrence, migration, and enrichment mechanisms. The influence of structural-dominated preservation conditions on shale pore structures is essential to comprehend for effective shale gas exploitation. This study employs field-emission scanning electron microscopy in conjunction with other techniques (low-temperature N2 adsorption, low-temperature CO2 adsorption, and nuclear magnetic resonance) for detailed analyses of the pore structure across varied structural zones, revealing the influence of structural attributes, fault systems, depth of burial, and formation pressure on pore architecture, and examining the relationship between pore structure and shale gas preservation conditions. The results show that stable structural condition is conducive to the development and preservation of shale pores. Structural compression causes inorganic and organic pores to become narrow and elongated due to shrinkage, with a significant increase in microfractures. The porosity of shale with stable structural conditions exhibits markedly increased porosity compared to samples under structural compressions. Under conditions of similar TOC and mineral composition, the pore size distribution (PSD), pore volume (PV), and specific surface area (SSA) of shale after structural compression are significantly lower than those of samples with stable structural conditions. As the burial depth increases, the shale porosity shows a decreasing trend, but the decrease is limited. Burial depth significantly impacts the SSA and PV of high-TOC samples (3%–6%). As the burial depth increases, both SSA and PV show a significant decreasing trend. When the burial depth reaches 4000 m, SSA and PV tend to concentrate. The formation pressure coefficient is an important factor for the development and preservation of shale pores, and porosity is positively correlated with the formation pressure coefficient. Increased formation pressure coefficient indicates superior preservation conditions and enhanced pore development.